Quixotes, dreamers and imaginists - Williams, S; Williams, Siân Bethan (1998)
﻿ The following study is an examination of the deluded heroine in the novel between 1740 and 1820. Through close readings of fiction by Samuel Richardson, Charlotte Lennox, Frances Burney, Charlotte Smith, Ann Radcliffe and Jane Austen, and discussion of relevant works by other authors of the period, the reasons for the prevalence of this figure are considered. The thesis proposes that this choice of protagonist enabled the exploration of a number of the issues that most concerned contemporary novelists. Principal amongst these was the question of identification between reader and literary protagonist. Throughout this period authors engaged in attempts to develop and control the audience's response. The desired end was the "improvement" of readers by the experience of the situations, mistakes and trials of the text's central characters. Increasingly though, the unpredictable and fluctuating nature of the readers' reactions was recognised. The result was a conflict between "text as instruction", the moral education that authors professed to offer, and "text as fiction", the attractions of story, adventure and imagination which were ostensibly valued only as they brought readers to works intended to improve them. The connection of the latter to romance was a further source of tension. The establishment of the novel as a model for life was premised on claims to probability, but aspects of the texts remained which worked against mimetic representation. These oppositions explain the contemporary popularity of the quixotic narrative, since the quixote both enacted the "madness" of excessive imaginative involvement with literature and could also be shown learning to make a "correct" choice of genre for reading. The strategies that can be observed within the quixote novel have a wider application when they are considered alongside the patterns of imitation, influence and parody which characterise the fiction of the period. In order to examine these features, the thesis includes an analysis of two important literary dialogues: those between Richardson and Lennox, and between Radcliffe and Austen. My focus on the heroine acknowledges the significance of gender in the period's fiction. Created by both female and male authors, such figures could be either exemplary models or quixotic warnings. They nevertheless share an experience of delusion followed by enlightenment constructed in order to benefit the "reading Misses" following their adventures. Unlike much recent criticism, however, my concern is more with the author as creative artist, text as literary process and reader as imaginative participant, than with historical or sociological contexts.